2008
DOI: 10.1534/genetics.108.087650
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Drosophila Hmt4-20/Suv4-20 Histone Methyltransferase

Abstract: Di-and trimethylation of histone H4 lysine20 (H4K20) are thought to play an important role in controlling gene expression in vertebrates and in Drosophila. By inducing a null mutation in Drosophila Suv4-20, we show that it encodes the histone H4 lysine20 di-and trimethyltransferase. In Suv4-20 mutants, the H4K20 di-and trimethyl marks are strongly reduced or absent, and the monomethyl mark is significantly increased. We find that even with this biochemical function, Suv4-20 is not required for survival and doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…6), suggesting that SET-4 may antagonize H4K20 monomethylation on autosomes. This finding is consistent with the observed increase in H4K20me1 levels in flies carrying a mutation in the set-4 homolog Suv4-20 (64). Western blot analysis also revealed that SET-4 activity is needed for wild-type levels of H4K20me3 (Fig.…”
Section: Figsupporting
confidence: 90%
“…6), suggesting that SET-4 may antagonize H4K20 monomethylation on autosomes. This finding is consistent with the observed increase in H4K20me1 levels in flies carrying a mutation in the set-4 homolog Suv4-20 (64). Western blot analysis also revealed that SET-4 activity is needed for wild-type levels of H4K20me3 (Fig.…”
Section: Figsupporting
confidence: 90%
“…Thus, a change in methyltransferase protein levels or modulation of methyltransferase activity by other histone modifications or by modifications on the enzymes themselves could account for the latency of H3K9 and H3K27 trimethylation. The absence of appreciable turnover at these residues is similar to the lack of H4K20me3 turnover across the cell cycle (39), where H4K20me3 was initially implicated in position effect variegation silencing, such as that for H3K9me3, but has recently been questioned as an epigenetic silencing mark (44). Furthermore, ectopic overexpression of EZH2, and presumably increased H3K27 trimethylation, accelerates G 1 -phase progression and leads to increased accumulation in S phase (8).…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, several lines of evidence have pointed to an interaction between HP1 and the H4K20 HMT Suv4-20 in mammalian systems, including in vitro pull down assays using mammalian proteins and a requirement for Suvar3-9h for proper distribution of H4K20me ). Suv4-20 has been reported to act as a suppressor of PEV in Drosophila; however, this activity appears to be dependent upon the allele and reporter combination being examined Sakaguchi et al 2008). Our results demonstrate an in vivo interaction between HP1 and Suv4-20 in Drosophila and support a yet-to-be-defined role for H4K20 in heterochromatic regions.…”
Section: Drosophila Heterochromatin Spreading 973mentioning
confidence: 99%